Does homeopathy reduce the cost of conventional drug prescribing? - Jain, Asha (Homeopathy, 2003)
There is little research on cost–effectiveness of homeopathy in General Practice. This study aimed to compare the costs of homeopathic prescribing with conventional drugs prescribing. Data were collected for 4 years on all patients who were treated homeopathically. Costs of homeopathic remedies and costs of conventional drugs which otherwise would be prescribed for these patients was calculated for the total duration of treatment. Savings were calculated. One hundred patients were included in the study. Average cost savings per patient was £60.40. The majority of patients had improved and most did not report any side-effects. The limitations of this study are that it is based on one GP's work, with a small number of patients so definite and generalisable conclusions cannot be drawn. Moreover, calculated costs in this study are based on drugs only, it does not take into account doctor's time, special investigations and time off sick. Future work needs to be carried out to include all of these points for a comprehensive economic analysis.
Keywords: General Practice; costs; conventional drugs; homeopathy; remedies; efficacy; side-effects; diversity; medical conditions